Evaluation of Risk Factors for Antituberculosis Drugs-Induced Hepatotoxicity in Nepalese - Shakya, Rajani; Rao, B.S.; Shrestha, Bhawana (Kathmandu University Journal of Science, Engineering and Technology, 2006)
Antitubercular drugs cause derangement of hepatic functions revealed by clinical examination and abnormal liver function test. Many factors are found to predispose patients towards this adverse reaction of anti-tubercular drugs, which can cause economical burden as well as prolong duration of illness. Detection of these risk factors for hepatotoxicity can play an important role in minimizing the incidence. The present study had objectives to assess the role of age, sex, alcohol intake, nutritional status and disease extent as risk factors in the development of hepatotoxicity in patients with active tuberculosis receiving antituberculosis treatment. 50 patients diagnosed of active tuberculosis infection with normal pretreatment liver function were monitored clinically as well as biochemically in a prospective cohort analysis. Four patients (8%) developed drug-induced hepatotoxicity. Antitubercular drugs-induced hepatotoxicity was prevalent in younger patients (6% vs. 2%, P> 0.05, P = 0.368, Odds Ratio [OR]; 2.75). Female gender was found to be at higher risk (P> 0.05, P = 0.219, Odds ratio [OR]; 4.2). Majority of the patients who had developed hepatotoxicity were sputum smear positive ones with advanced tuberculosis infection. Nutritional status, assessed by body mass index (BMI) and serum albumin level, was the next predisposing factor. Risk factors of hepatotoxicity included female sex, disease extent and poor nutritional status. Timely detection and temporary withdrawal of the offending agent can completely cure antitubercular drugs-induced hepatotoxicity.